2012
DOI: 10.1120/jacmp.v13i6.3994
|View full text |Cite
|
Sign up to set email alerts
|

Reference dosimetry using radiochromic film

Abstract: The objectives of this study are to identify and quantify factors that influence radiochromic film dose response and to determine whether such films are suitable for reference dosimetry. The influence of several parameters that may introduce systematic dose errors when performing reference dose measurements were investigated. The effect of the film storage temperature was determined by comparing the performance of three lots of GAFCHROMIC EBT2 films stored at either 4°C or room temperature. The effect of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…23 On subsequent calibrations, irradiations were performed only with films placed at the surface, as the D s /D max ratio was already known, and the films were intended to assess surface doses. Girard et al 23 reported dose differences of up to 3.5% in the red channel for EBT2 films and calibration curves obtained 3 months apart. In this work, the difference between consecutive calibration curves obtained 4-5 months apart for EBT3 films was 3-4% for the red channel and 1.5-2% for the green channel.…”
Section: Film Calibration and Read-outmentioning
confidence: 99%
“…23 On subsequent calibrations, irradiations were performed only with films placed at the surface, as the D s /D max ratio was already known, and the films were intended to assess surface doses. Girard et al 23 reported dose differences of up to 3.5% in the red channel for EBT2 films and calibration curves obtained 3 months apart. In this work, the difference between consecutive calibration curves obtained 4-5 months apart for EBT3 films was 3-4% for the red channel and 1.5-2% for the green channel.…”
Section: Film Calibration and Read-outmentioning
confidence: 99%
“…Recent publications proposed elegant solutions to this limitation, for example Girard et al [13] and Crijns et al [17]. These kinds of investigations are outside the scope of this work, since our purpose is to report about our experience with commercially available software and "plug and play" solution.…”
Section: Discussionmentioning
confidence: 99%
“…Radiochromic films are better stored in a dry and dark environment. Girard et al [13] reported a maximum rate of optical density change of ±0.15% per C in the red channel. They also showed that relative humidity variations ranging from 80% to 20% could introduce dose errors of up to 15%.…”
Section: Radiochromic Film and Scanner Models Usedmentioning
confidence: 99%
“…The present task was divided into two parts, namely, (1) the atomic scale model and (2) the macroscopic scale model, in which molecular dynamics (MD) and finite element method (FEM) simulation techniques were coupled. The active layer in the EBT3 film consisted of diacetylene (DA) pentacosa-10,12-diynoate monomers [20] (hereafter referred to as DA monomers), which were modelled using the MD technique. The degrees of SSP in the atomic scale upon different UV exposures were obtained in order to determine the absorption coefficients of the active layer, which were then input into the FEM model.…”
Section: Atomic Scale Modelmentioning
confidence: 99%
“…The active layer in the EBT3 film consisted of diacetylene (DA) pentacosa-10,12-diynoate monomers [20] (hereafter referred to as DA monomers), which were modelled using the MD technique. The degrees of SSP in the atomic scale upon different UV exposures were obtained in order to determine the absorption coefficients of the active layer, which were then input into the FEM model.…”
Section: Introductionmentioning
confidence: 99%